Synthesis of PLGA/chitosan/zeolites and PLGA/chitosan/metal organic frameworks nanofibers for targeted delivery of Paclitaxel toward prostate cancer cells death - Dizaji, Babak Faraji; Azerbaijan, Mohammadreza Hasani; Sheisi, Niloofar; Goleij, Pouya; Mirmajidi, Tahereh; Chogan, Faraz; Sharafian, Fariborz (Elsevier, 2020)
In the present study, the various zeolites including hydrophilic Y zeolite, hydrophobic ZSM-5 zeolite and metal organic frameworks (MOFs) including MIL-101 and ZIF-8 were incorporated into the PLGA/chitosan nanofibers for controlled release of Paclitaxel anticancer drug against prostate cancer in vitro and in vivo. The synthesized nanoparticles and nanofibers were characterized using FTIR, XRD, SEM, BET and water contact angle analysis. The drug loading efficiency of nanofibers containing zeolites and MOFs indicated that the MOFs were more useful compared with zeolites for higher loading of Paclitaxel molecules. The Paclitaxel release behavior from nanofibers containing zeolites and MOFs were also examined. The MTT assay and DAPI staining analysis were used to determine the cytotoxicity and apoptosis effect of nanofibers containing Paclitaxel against LNCaP prostate cancer cell lines. The tumor inhibition rate in vivo was carried out to obtain the optimum nanofibrous formulation with maximum cell death percentage and tumor inhibition rate. The obtained results revealed the better activity of MOFs compared nanozeolites for higher loading of Paclitaxel drug into the nanoparticles and a more sustained release of drug from nanofibers containing MOFs. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: PLGA/chitosan nanofibers; Zeolite; Metal organic framework; Paclitaxel; Prostate cancer